2012
DOI: 10.1063/1.4752458
|View full text |Cite
|
Sign up to set email alerts
|

Contact charging of silica glass particles in a single collision

Abstract: Based on asymmetric contact, we present a contact charge model of high-energy trapped holes to predict the contact charging and explain the net charge transfer between identical silica glass surfaces in a single normal collision. Furthermore, the contact charging measurements are investigated on normal collisions of glassy particle-glassy particle-steel plane and glassy particle-glassy plane. The predicted results agree well with our experiments qualitatively and quantitatively: the impacting velocity and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 40 publications
2
46
1
Order By: Relevance
“…Lacks and coworkers later showed how the same geometrical asymmetry also arises with random collisions among particles of different size [16][17][18]. However, while in most situations the transferred charge species is negative, there are some materials, such as nylon, where the polarity is reversed, which points to the possibility that other charge species might be responsible (Hu et al recently suggested trapped holes might explain the polarity reversal [19]). …”
mentioning
confidence: 99%
“…Lacks and coworkers later showed how the same geometrical asymmetry also arises with random collisions among particles of different size [16][17][18]. However, while in most situations the transferred charge species is negative, there are some materials, such as nylon, where the polarity is reversed, which points to the possibility that other charge species might be responsible (Hu et al recently suggested trapped holes might explain the polarity reversal [19]). …”
mentioning
confidence: 99%
“…Remarkably, however, grains that are absolutely identical in shape, size and chemical composition have also been found to charge one another [16,[18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the charge carriers among them could be electrons Lacks, 2009), ions (McCarty andWhitesides, 2008), trapped holes (Hu et al, 2012), and bits of nanoscopic material (Apodaca et al, 2010), depending on the material properties and condition involved (Lacks and Sankaran, 2011;Wei and Gu, 2015). These models mainly focus on explaining 365 size-dependent charging (that is, smaller particles tend to acquire a net negative charge during collisions with larger particles) of dust particles without considering the environmental factors, which have been found to considerably affect dust electrification.…”
mentioning
confidence: 99%
“…To quantitatively predict the charge transfer processes between dust particle collisions/contacts, a large number of theoretical models have been developed based on different physical mechanisms, such as asymmetric contact (Hu et al, 2012;Kok and Lacks, 2009;Kok and Renno, 2008), polarization by external E-fields (Pähtz et al, 2012), statistical variations of material 360…”
mentioning
confidence: 99%